Eros "paidikos" kontra miłość do kobiety w "Dialogu o miłości erotycznej" Plutarcha i "Bogach miłości" Lukiana - Sowa, Joanna (Collectanea Philologica, 2014)
In this paper, I examine the debate between advocates of male and female love in two works dedicated to this subject: Plutarch’s Amatorius (Dialogue on Love) and Lucian’s Amores (Affairs of the Heart). Plutarch, drawing on Platonic tradition, accepts and praises eros paidikos, but he condemns homosexual intercourse as an act of hybris. On the other hand, Plutarch rejects traditional Greek prejudices against women and glorifies marriage as the highest form of human relationship: he argues that conjugal love contains both the lifelong friendship and sexual relations which are a source of mutual kindness, respect and affection. In Lucian’s work the defender of pederasty, portraying it as a spiritual relationship and a mark of advanced cultural evolution, wins the debate; but in the last part of dialogue moral demands of sexual restraint in pederasty are mocked, and sexual pleasure is called “a mediator of friendship”.